Biodegradation of chlorpyrifos and 3, 5, 6‐trichloro‐2‐pyridinol by a novel rhizobial strain Mesorhizobium sp. HN3. (7th March 2014) - Jabeen, Hina; Iqbal, Samina; Anwar, Samina
Abstract A chlorpyrifos (CP) and 3, 5, 6‐trichloro‐2‐pyridinol (TCP) degrading bacterial strain, Mesorhizobium sp. HN3, was isolated and characterized. Mesorhizobium sp. HN3 degraded CP efficiently up to 400 mg/L initial concentration at wide range of temperatures (30–40°C) and pH (6.0–8.0). However, optimal degradation of CP was achieved at 37°C and neutral pH (7.0) at an initial inoculum density 2 × 107 colony forming unit/mL of culture medium. Kinetic parameters for CP degradation by Mesorhizobium sp. HN3 were estimated at different initial concentrations. Cultures exhibited significant variation (P ≤ 0.05) in the specific growth rate (μ), cell mass formation rate (QX) and the substrate uptake rate (QS) during degradation of CP. The values of kinetic parameters increased up to 100 mg/L CP and decreased at higher concentration. Investigation of degradation metabolites indicated that CP is converted to diethylthiophosphate and TCP that leads to the formation of 3, 5, 6‐trichloro‐2‐methoxypyridine.